Development of a Virtual Reality Simulator for a Strategy for Coordinating Cooperative Manipulator Robots Using Cloud Computing - Urrea-Onate, E; Matteoda-Robledo, R (Elsevier B.V., 2020)
This article deals with the development of a simulator that recreates, in virtual reality, a team of Selectively Compliance Assembly Robot Arms (SCARA). This team works cooperatively to fulfill the task of stacking rectangular objects coordinated through a strategy that includes a cloud server responsible for communication between the robots. The execution of the task is based on a leader/follower configuration. In this configuration, the leader performs a computed trajectory constantly reporting its position to the remote server. The remote server, in turn, sends this information back to the follower so this can follow the leader. The application combines MatLab® and Java. The latter is specifically used for communication routines, since its versatility makes it easy to be incorporated into any type of machine. This paper seeks to demonstrate the advantages of incorporating cloud resources into a multi-robot system and how its performance can be tested by means of the application developed. © 2020 Elsevier B.V.